Fall risk screening and balance rehabilitation in elderly: a missing healthcare intervention in Pakistani healthcare system. - Azim, Muhammad Ehab; Asghar , Ejaz; Babur, Muhammad Naveed; Rathore, Farooq Azam (Journal of the Pakistan Medical Association, 2023)
Elderly are one of the fastest-growing population globally and require significant healthcare services due to age-related deterioration in physiological systems. Poor postural control due to aging results in impaired balance leading to increase in frequency of falls, poor quality of life, and rise in disability and mortality rates. In Pakistan, due to lack of awareness, and resources, fall prevention and screening programmes for the elderly are lacking. Regular fall risk screening utilizing balance assessment tools, integration of fall prevention programmes and balance rehabilitation approach as part of elderly healthcare services can serve as tools to lower the incidence of falls in the elderly population of Pakistan. Moreover, integration of latest technology as part of balance rehabilitation can also be considered. The review aims to highlight appropriate strategies for fall risk screening and balance rehabilitation in an effort to promote an important healthcare intervention for elderly in Pakistan. Keywords: Aging, Balance Rehabilitation, Elderly, Fall Risk, Pakistan.